Karakteristik kimia, kandungan karotenoid dan tokoferol mikroenkapsulat minyak buah merah (pandanus conoideus Lamk.) Degumming dengan variasi konsentrasi maltodekstrin sebagai penyalut - Jupiter Arung Padang, Monica; Letviany Sarungallo, Zita; Santoso, Budi (Program Pascasarjana Universitas Papua, 2026)
ABSTRACT : The development of red fruit (Pandanus conoideus Lamk.) oil as a food additive, both as a fortificant and a natural colorant, through microencapsulation technology has been proven to produce stable microencapsulates. However, its chemical characteristics and active component content have not been widely reported. Therefore, this study aims to determine the chemical properties and active components of the resulting red fruit oil microencapsulates. This study aims to determine the chemical properties and active components of the microencapsulated red fruit oil produced. The research was conducted in two stages: (1) the production of microencapsulated degummed red fruit oil through emulsification and drying processes, and (2) the analysis of the chemical properties and active components of the resulting microcapsules. The formulations used involved different ratios of maltodextrin and water: M1 (16% : 59.5%), M2 (17% : 58.5%), M3 (18% : 57.5%), and M4 (19% : 56.5%). The results showed that microencapsulated degummed red fruit oil with a 20% oil concentration could be produced using maltodextrin as the encapsulating agent in the range of 16–18%. The best formulation was M3 (18% maltodextrin), which had characteristics of 9.112% moisture content, 40.043% fat content, and contained 1,835 ppm total carotenoids and 835 ppm tocopherol.